2023
DOI: 10.1002/jsfa.12433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microencapsulated inoculum of Pichia kudriavzevii on the fermentation and sensory quality of cacao CCN51 genotype

Abstract: BACKGROUND: Microencapsulated yeasts are a novel alternative as a delivery matrix for microbiological starters. This technology aims to protect the active compounds from adverse environmental conditions and prolong their useful life and could also improve the conditions of the starters for cocoa fermentation. The present study established the effective dose to apply the microencapsulated yeast Pichia kudriavzevii as a microbiological starter of fermentation and biotechnological strategy for promoting the bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The values obtained at the end of fermentation were similar to those stated by other authors, who have reported pH values of 5.0 (26,36,37). The gradual increase in pulp pH during fermentation can be attributed to the decrease in the concentration of citric acid since yeasts and bacteria break it down to metabolize the sugars present in the pulp (30,13).…”
Section: /14supporting
confidence: 88%
See 1 more Smart Citation
“…The values obtained at the end of fermentation were similar to those stated by other authors, who have reported pH values of 5.0 (26,36,37). The gradual increase in pulp pH during fermentation can be attributed to the decrease in the concentration of citric acid since yeasts and bacteria break it down to metabolize the sugars present in the pulp (30,13).…”
Section: /14supporting
confidence: 88%
“…Cocoa fermentation is a spontaneous microbiological process; it is known that the microorganisms that initiate it are yeasts, thanks to the high content of carbohydrates, low pH, and the limited availability of oxygen in the pulp (11). The main activity of yeasts is the production of ethanol from carbohydrates, in addition to the assimilation of citric acid and the degradation of pectin (12,13). This activity leads to the production of CO 2 favoring anaerobic conditions, allowing the development of lactic acid bacteria, which hydrolyze complex sugars, consume citric acid, and produce lactic acid, acetic acid, and mannitol (14).…”
Section: Introductionmentioning
confidence: 99%
“…Using starter cultures [9,37,[58][59][60][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Using enzymes [76- Given the important role of microorganisms in cocoa fermentation, several studies propose the use of starter cultures as a strategy to improve cocoa quality and maintain reproducibility among fermentation batches [8,[58][59][60]. Potential starter cultures have also been studied to elucidate microbial diversity, structure, and functional and metabolic pathways.…”
Section: Purpose How Referencesmentioning
confidence: 99%
“…Decimal dilutions were made up to 10 -6 ; the last three dilutions were cultured in malt extract medium placed in Petri dishes and in superficial extension with glass beads. The dishes were incubated at 35°C for 48 h, counting the colonies on the plate, which were multiplied by the dilution factor and by 10, expressing the results in colony-forming units per milliliter (CFU/mL) (16).…”
Section: Substrate Utilization Testmentioning
confidence: 99%